Analysis of Political and Economic Situation in Afghanistan at the First Half of the Second Decade of XXI Century - Rashidov R.R. (Peerian Journals Publishing, 2023)
Afghanistan is passing through a turbulent period in its history. After almost years of turmoil since 9/11 and the significant presence of foreign forces, the country was still plagued by insurgency, unstable government, a weak economy and underdeveloped infrastructure. The great uncertainties about the security and political transitions underway in Afghanistan and the country’s economic outlook are likely to continue generating pervasive ambivalence in Washington, Kabul, and other capitals over how to manage the U.S. and ISAF withdrawals and their after-effects.
Keywords: civil war; political situation; presidential election; insurgency